PENGEMBANGAN METODE LOCAL NEURAL-NETWORK KHON-SHAM EXCHANGE FUNCTIONAL PADA MOLEKUL - Danu Wijaya, Agung
Development exchange functional Ex is generally based on a general strategy that is often referred to as Jacobs Ladder, where for increased accuracy of the function Ex involves KS orbitals and derivative of electron density with respect to space. Various functions of Ex with varying accuracy are widely available today. But the continued development of these functions still faces many obstacles. Although the ideal function of Ex is unknown, but from the KS equation it is known that Ex is a function of the electron density of ?. Machine learning (ML) is a popular method that is widely used in various areas of science and can be found in various applications in the field of chemistry. In this study we made a function model Ex using the artficial neural networks (ANN) approach. The input used in ANN is ? which is obtained from the wave function of the KS equation. In the calculation of energy atomization (AE) with the LDA-ANN model the AE deviation value is 0.151 Hartree and for LDA-HEG the deviation is 0.322 Hartree with deviation based on the experimental results.